A educação ambiental na formação do técnico agrícola - Moreira, Jarbas Sobreira (2009)
In the face of the changes and social problems resulting from the production systems of Modern Agriculture (pollution of soils, waters, erosion, destruction of the ozone layer, destructions of fauna and flora), globalization and the financial policy changes, which brought the idea of the increase production and profit without minding to the nature degradation, it became necessary a further reflection on the training of Technical Agriculture with a focus on environmental issues. This study was carried out for the purpose of examining the presence of environmental education and the development of environmental awareness in education and training of agricultural experts in the course of agriculture/ cattle breeding at Colégio Agricola Vidal de Negreiros - CAVN (Bananeiras - PB). Researches using qualitative elements, and some methods, such as, the application of questionnaires to teachers and students of 2nd year at CAVN were made with the intention of identifying as a Environmental Education has been developed by teachers in a satisfactory way, and if this is enough for students to develop an environmental awareness by contributing to the protection and sustainable use of natural resources. In this way the analysis of data showed that environmental education has been developed in a unsatisfactory way at CAVN, preventing the development of environmental awareness in students and teachers. In this context, to develop an agricultural technical, conscious and capable of acting in social environment reality is necessary a continuous training of teachers, the interdisciplinary approach to environmental issues, promoting integration of actions, disclosure and discussion of the developed activities.